The Effect of Job Creation Law Regulation on Mining Business: Economic Impact Analysis on the Mining Industry - Muhammad Satrio Mubaraq; Wahyudin Wahyudin; Muhammad Irham Guntur (Indonesian Journal of Business and Entrepreneurship Research, 2024)
This study provides important insights into the impact of Labor Law Regulation on the mining industry, with a focus on PT. Vale Indonesia. By applying simple linear regression analysis to the company’s financial and operational data from 2019 to 2022, the research evaluates the effects of the Labor Law Regulation both before and after its implementation. The study aims to determine how the regulation influences the financial and operational performance of PT. Vale Indonesia. The Labor Law Regulation, as the independent variable, assesses the effectiveness of government policies in supporting the mining sector. Financial performance, the dependent variable, is measured through indicators such as economic impact and perception. The analysis reveals a significant improvement in PT. Vale Indonesia’s financial outcomes post-regulation, suggesting enhanced operational efficiency and capital investment. However, the study also notes the need for further investigation into the social impact on surrounding communities. Overall, the research concludes that the Labor Law Regulation has a positive and statistically significant effect on the mining business, indicating strong government policy support, with a high predictive power.